Advances in Membrane Proteins Part I: Mass Processing and Transportation (Springer Singapore, 2018)
The book summarizes advances in biochemical and biophysical property of membrane proteins as well as their applications in biomedicine. It is organised into 2 themed parts. The first volume focuses on mass processing and transportation and provides deep and comprehensive information on specific groups of membrane proteins including channels and transporters, nuclear and cytoplasmic membrane proteins, and membrane embedded enzymes. Their structures, functions, related diseases as well as their roles in drug discovery are fully discussed. Interesting topics cover fundamental concepts, latest progress and critical puzzles yet to be solved. This work will appeal to a wide readership within the membrane structural and functional biology field. Junior scientists could use it to fast track into the field. Advanced scientists will find it helpful to gain a broader view of the field beyond their area of specialization.